Front propagation versus bulk relaxation in the annealing dynamics of a kinetically constrained model of ultrastable glasses - Gutierrez, Ricardo; Garrahan, Juan P. (IOP Publishing, 2016)
Glasses prepared by physical vapour deposition have been shown to be remarkably more stable than those prepared by standard cooling protocols, with properties that appear to be similar to systems aged for extremely long times. When subjected to a rapid rise in temperature, ultrastable glasses anneal towards the liquid in a qualitatively different manner than ordinary glasses, with the seeming competition of different time and length scales. We numerically reproduce the phenomenology of ultrastable glass annealing with a kinetically constrained model, a three dimensional East model with soft constraints, in a setting where the bulk is in an ultrastable configuration and a free surface is permanently excited. Annealing towards the liquid state is given by the competition between the ballistic propagation of a front from the free surface and a much slower nucleation-like relaxation in the bulk. The crossover between these mechanisms also explains the change in behaviour with film thickness seen experimentally.